ANALYSIS OF THE INFLUENCE OF KNOWLEDGE, PLEASURE, ON CUSTOMER BEHAVIORAL INTENTION IN USING MOBILE BANKING WITH ATTITUDES AS INTERVENING VARIABLES IN JAMBI PROVINCE: Edwin Bustami - Edwin Bustami (LPPM STIA Nusantara Sakti, 2022)
This study aims to test and investigate the direct and indirect influence of knowledge, pleasure on attitudes, regarding mobile banking and Behavioral Intention (intention) to use Jambi mobile banking services. This research uses survey and verifiability methods. The sample used 400 units. Analyze the data using Path Analisys. The results showed that knowledge, pleasure had a direct and significant effect on attitudes; knowledge, pleasure and direct and significant attitudes towards Behavioral Intention; knowledge, pleasure have an indirect and significant effect on Behavioral Intention through attitudes; The results of the study recommend that management in the future needs to improve and maintain customer knowledge, pleasure, attitude, and customer in using mobile banking by means of direct or indirect education through multi-media.